Long-term survival of a SMARCA4-deficient undifferentiated thoracic tumor with brain metastasis successfully treated with multimodal treatment: a case report and literature review - Yu Gan; Qi Hu; Fangfang Hu; Shugui Wu (Journal of Cancer Research and Clinical Oncology)
Abstract Background SMARCA4-deficient undifferentiated thoracic tumor (SMARCA4-UT) is a rare and highly aggressive malignancy characterized by early distant metastasis and a poor prognosis, with a median overall survival (OS) of only 4–7 months. Traditional therapies offer limited benefit, while emerging data suggest the efficacy of combined immunotherapy, chemotherapy, and anti-angiogenic approaches. Case summary We report a case of a 52-year-old male with a heavy smoking history who presented with loss of consciousness and limb convulsions. Imaging revealed brain metastasis and a thoracic tumor. After surgical removal of the brain lesion and a lung biopsy, the patient was diagnosed with SMARCA4-UT, showing no targetable driver mutations and a programmed death-ligand 1 (PD-L1) tumor proportion score (TPS) < 1%. The patient underwent first-line treatment with tislelizumab, bevacizumab, carboplatin, and paclitaxel. Despite discontinuation of bevacizumab due to a tumor cavity, the patient achieved partial remission (PR) after six cycles. Notably, consolidative thoracic radiotherapy (TRT) was administered following systemic disease control to enhance local control. After 5 months of maintenance therapy, oligoprogression of the primary lung lesion was detected and the progression-free survival (PFS) of first-line treatment reached 14 months. The patient then performed salvage surgery for local lesion and continued with maintenance treatment. As of May 2025, the patient has survived for 31 months since the initial diagnosis. Conclusion Multimodal therapy integrating chemoimmunotherapy, anti-angiogenesis, consolidative radiotherapy, and salvage surgery achieved durable survival in SMARCA4-UT with brain metastasis. It highlights the potential of combining systemic and local therapies, providing valuable insights for managing this challenging disease.